Historical geography as an international discipline 1975–2015: responses. Issue 3 (23rd February 2016) - Cameron, Laura; Forsyth, Isla; Yamamura, Aki; Novaes, André Reyes
Abstract : This commentary is a compilation of four responses to a paper by Alan R. H. Baker on the internationalisation of historical geography, originally given during the plenary session of the 2015 International Conference of Historical Geographers, and published in The Geographical Journal (Baker 2015). The oral versions of these (international) responses were presented by Laura Cameron (Canada), Isla Forsyth (UK), Aki Yamamura (Japan) and André Reyes Novaes (Brazil); Mona Domosh (USA) also contributed to the oral session.